STATEMENT AND INVESTIGATION OF ONE BOUNDARY PROBLEM FOR ONE PARABOLIC-HYPERBOLIC EQUATION OF THE THIRD ORDER IN A PENTAGONAL DOMAIN WITH THREE LINES OF TYPE CHANGE - M. Mamajonov; D.D. Aroev; G. Shermatova (Galaxy International Interdisciplinary Research Journal, 2022)
In the present work, we pose and study one boundary value problem for a parabolic- hyperbolic third-order equations of the form